Impact of KVK Activities on Dynamics of the Adoption of Climate resilient Agricultural Technologies In Bundelkhand Region of M.P. (Indian Journal of Extension Education, 2018)
Krishi Vigyan Kendras are conducting various programmes with the felt needs of the farmers as per the resources available to enrich knowledge and skill competency of the farmers to adopt the changed practices for more production and income for their sustainable livelihood. Climate change threatens to derail the lives and livelihoods of farmers if appropriate adaptation measures are not put in place. Technology adoption is seen as an important tool for increasing agricultural efficiency and struggle food insecurity. The present study conducted at KVK in the districts of Datia and Tikamgarh. The information was collected through personal interview schedule. The study revealed that there was increase in productivity of farmers was observed due to adoption of various smart practices as suggested by KVKs. Programme was found to be useful in imparting knowledge and adoption level of farmers in various aspects of climate resilient agricultural technologies. Practices created greater awareness and motivated the other farmers to adopt appropriate production technologies.